Entrepreneurship in Scotland, 1851–1911. Issue 1 (May 2021) - Smith, Harry; Bennett, Robert J.; van Lieshout, Carry; Montebruno, Piero
Abstract : This article uses the British Business Census of Entrepreneurs (BBCE) to examine the history of entrepreneurship in nineteenth- and early twentieth-century Scotland. The BBCE identifies every business proprietor listed in the 1851–1901 Scottish censuses, correcting for non-response issues. The BBCE, therefore, allows the whole population of Scottish entrepreneurs to be examined for the first time. These data are combined with a reweighted version of the 1911 Scottish Census report to allow the trends in entrepreneurial numbers and rates to be examined as a whole and broken down by sector and gender. The article also shows how entrepreneurship varied by location. This article offers support for previous work on Scottish entrepreneurship, notably stressing the continued importance of small-scale businesses. It also reveals that female entrepreneurship rates were far higher than previously thought. This article lays the groundwork for future studies of Scottish entrepreneurship using the BBCE data.